Environmental-economic assessment of lignocellulosic residual from the Legal Amazon for conversion in biochars and bioproducts for biorefineries - Junior, Cláudio Carneiro Santana; Brito, Mateus Rodrigues; Barbosa, Lorena Nascimento; Jaconi, Angélica; Rambo, Magale Karine Diel; Rambo, Michele Cristiane Diel (International Journal of Advanced Engineering Research and Science, 2020)
Biochars are emerging ecological products that show excellent properties in areas such as carbon sequestration, soil improvement, bioremediation, activated carbon and bioenergy. These interesting materials can be synthesized from a wide variety of sources derived from waste, including lignocellulosic biomass waste. In this work, biochars were produced from residues from the Brazilian Amazon, such as green coconut, babassu and Brazil nuts. The synthesis of biochars was performed under pyrolysis conditions with a fixed time of 3 h and temperature variation of 250 ºC (T1) and 400 ºC (T2). Yields of biochar production >85%, carbon contents >56%, and oxygen contents >20% and calorific values >23 MJ.Kg-1, demonstrate that biochars produced from residual biomass can be used as activated carbon and also as fertilizers in soils, thus adding value to such residues. Besides, the biomasses used were characterized and the achieved remarkable yields of fermentable sugars, reaching up to 70% in cellulose hydrolysis, which can be useful in the production of bioproducts. In addition, the efficient use of these biomasses will positively impact the productive chains involved, benefiting society, generating employment, income, Besides as mitigating an environmental liability.